Adaptive super-twisting fast nonsingular terminal sliding mode control with ESO for high-pressure electro-pneumatic servo valve. (May 2023) - Sun, Hailin; Gao, Longlong; Zhao, Zhixin; Li, Baoren
Abstract: In this paper, an adaptive super-twisting fast nonsingular terminal sliding mode controller (ASTFNTSMC) with active disturbance rejection is proposed to improve the response speed, control accuracy, and disturbance rejection ability of the high-pressure electro-pneumatic servo valve (HESV). This controller effectively combines sliding mode control (SMC), active disturbance rejection control (ADRC), and adaptive control. An improved fast nonsingular terminal sliding surface is constructed to speed up the dynamic response. This surface is characterized by the mutual decoupling between the control input and the system state in its derivative, so a super-twisting algorithm (STA) can be implemented to mitigate chattering. By using ADRC, system nonlinearities and external disturbances are regarded as a total disturbance. An extended state observer (ESO) is incorporated into the controller to estimate the total disturbance, and the estimation is applied as feedforward compensation. As a result, the switching term of STA only needs to suppress the residual disturbance, so chattering is further mitigated and disturbance rejection ability is enhanced simultaneously. Furthermore, an adaptive law is employed to reduce the conservativeness in the parameter selection. Finally, comparative experiments are carried out for HESV on the test platform. Experimental results are consistent with the theoretical analysis, showing that the proposed method can achieve faster dynamic response, higher tracking accuracy, and better disturbance rejection performance.